QUANTITATIVE DETERMINATION OF THE AMOUNT OF FLAVONOIDS IN THE HERB OF SALVIA FARINACEA BENTH. - O. I. Popova; A. S. Nikitina; E. A. Azryakova (Фармация и фармакология (Пятигорск), 2016)
Chromatographic researches conducted have allowed determination of the flavonoids presence in raw materials of Salvia farinacea Benth. They were rutin, quercetin, hyperoside, and 5 phenol carbonic acids: caffeic, p-coumaric, ferulic, gallic, and cinnamic acids. The quantitative content of the sum of flavonoids in Salvia farinacea Benth. was conducted by the method of differential spectrophotometry, and it amounted to 0.55-0.60% in terms of rutin. The research conducted made it possible to expand the scientific data of phenolic compounds of Salvia farinacea Benth. and to offer the possibility of recycling, monitoring procurement and targeted use of Salvia farinacea Benth. herb in pharmacy and medicine.